Desarrollo industrial de America Latina y el Caribe : posibilidades y limitaciones (SELA CaracasVE, 1987)
Reviews underlying ideas that influenced the various stages of the Latin American industrialization process. Such ideas range from that of being a raw materials exporter to import substitution. Gives exposition of the new-liberal open model applied during the seventies. Presents some of the results of the industrialization process which causes it to be classified as a` Pyrrhic' victory. Highlights some positive results and elements of dynamism in the region. Reviews main interpretations of Latin American industrialization emphasizing the proposals of alternative patrons of development. Discusses the formulation of a new industrial development policy in Latin America.
Includes bibliographical references